2015
DOI: 10.1007/s11356-014-3942-0
|View full text |Cite
|
Sign up to set email alerts
|

Total mercury and methylmercury distributions in surface sediments from Kongsfjorden, Svalbard, Norwegian Arctic

Abstract: The total mercury (THg) and methylmercury (MeHg) distributions in the surface sediments of Kongsfjorden, Svalbard, in the Norwegian Arctic were investigated in this study. The results showed that THg concentrations ranged from 9.11 to 86.73 ng g(-1), whereas MeHg concentrations had an average of only 0.11 ng g(-1). Factors that control the distribution and methylated transformation of mercury were examined, and the results suggested that the movements of ocean currents and glaciers affect the THg distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…3). These results support earlier studies showing that sediments with high OM are typically characterized by high Hg concentrations in the North Slope of Alaska, the Yukon River basin in the Canadian Arctic, and Kongsfjorden on Spitsbergen 10,16,37,38 .…”
Section: Discussionsupporting
confidence: 91%
“…3). These results support earlier studies showing that sediments with high OM are typically characterized by high Hg concentrations in the North Slope of Alaska, the Yukon River basin in the Canadian Arctic, and Kongsfjorden on Spitsbergen 10,16,37,38 .…”
Section: Discussionsupporting
confidence: 91%
“…The present study observed a mean total mercury concentration of 0.022 ppm in Site 1 and 0.014 ppm in site 2. Liu et al inspected both total mercury and methyl mercury concentrations in the surface sediments of Kongsfjorden, Svalbard and showed that concentrations of total mercury ranged from 9.11 to 86.73 ng g −1 , while average concentrations of methyl mercury was 0.11 ng g −1 . Increasing concentration of mercury in an ecosystem may develop tolerant microorganisms that could detoxify the contaminant from the system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, observations in fjords in northwestern Svalbard suggest that glacial meltwater plumes could reduce the phytoplankton biomass (Piquet et al, 2014), and this might effectively limit MeHg production and uptake in the marine food chain. Furthermore, the high deposition rates of inorganic matter near tidewater glaciers, or at the mouth of proglacial channels, dilute the organic matter content in the seafloor sediments of Svalbard fjords (Liu et al, 2015), and this might limit benthic Hg methylation. On the whole, therefore, the environmental impact of Hg releases from melting glaciers and ice caps is likely to be local, rather than widespread across the Arctic.…”
Section: Glaciersmentioning
confidence: 99%